Modern Dance “Body – Mind Teaching Method” Rooted in National Culture - Min Yuan (Art and Society, 2024)
As dance programs in higher ed works to de-center Euro centric styles, learning how dance in China draws upon Confucianism would be a valuable addition to the field. Philosophical perspective, this paper describes modern dance teaching that values the national symbolic experience of the dance body and constructs the national cultural thinking of the dance individual as an experiential practice of college arts education that focuses on the performance of students’ spiritual existence.